2004
DOI: 10.1002/ajhb.20094
|View full text |Cite
|
Sign up to set email alerts
|

Cellular life histories and bow tie biology

Abstract: Considering the life-long influences of fetal growth biology, it is of interest to further elucidate the nature of the fetal growth process itself. Previous analyses of longitudinal fetal ultrasound data led to the hypothesis that hypoxia signals were important aspects of normal growth biology and directed attention to the place of oxygen as a basic nutrient. From the perspective of the cell, both hypoxia and lack of energy substrate trigger a common adaptive pathway through their effects on ATP availability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 94 publications
1
23
0
Order By: Relevance
“…While the present observations derive from a modest sample, the results describe an anatomical pattern that parallels a number of reports from animal models (Lampl, 2005). The specific sequence of organomegaly found in the present sample of smoke-exposed fetuses has been previously reported among hypoxemic mice, where renal hyperplasia preceded cardiomegaly: compared to HIF-deficient mice, normal animals exposed to chronic hypoxia up-regulated EPO and VEGF in kidney and heart within hours.…”
Section: Implications Of Facultative Fetal Growth Negotiated By Organsupporting
confidence: 86%
See 1 more Smart Citation
“…While the present observations derive from a modest sample, the results describe an anatomical pattern that parallels a number of reports from animal models (Lampl, 2005). The specific sequence of organomegaly found in the present sample of smoke-exposed fetuses has been previously reported among hypoxemic mice, where renal hyperplasia preceded cardiomegaly: compared to HIF-deficient mice, normal animals exposed to chronic hypoxia up-regulated EPO and VEGF in kidney and heart within hours.…”
Section: Implications Of Facultative Fetal Growth Negotiated By Organsupporting
confidence: 86%
“…proposed pathway preferences hypoxia signals as important to the growth cascade (Lampl, 2005). The details of such a process remain to be elucidated, but the present data allude to such a putative biology.…”
Section: Normal Versus Compensatory Growthmentioning
confidence: 93%
“…This may be an expression of ''nested bow-tie'' metabolic architecture (Csete and Doyle, 2004;Lampl, 2005), in which cross-talking chemical pathways permit multiple avenues for information about the environment to have an impact on the amount and timing of growth events. With sufficient inhibitory feedback, a growth saltation will theoretically be suppressed.…”
Section: Growth Biology Is a Fundamental Interface Between The Speciementioning
confidence: 99%
“…Conditions during intrauterine growth and development influence adult physiology (Crespi and Denver, 2005;Ellison, 2005;Horton, 2005;Jones, 2005;Kuzawa, 2005;Lampl, 2005;McDade, 2005;Pike, 2005;Worthman and Kuzara, 2005) and are related to the risk of major chronic diseases, including cardiovascular diseases and diabetes (Barker, 1995;Forsen et al, 1997) and also breast cancer in women. Several studies [but not all; see: Ekbom et al (1997), Sanderson et al (2002), andTitusErnstoff et al (2002)] have shown that the risk of breast cancer increases with increasing birth weight (Ahlgren et al, 2004;Andersson et al, 2001;De Stavola et al,et al, 2003;Michels, 1996), which is believed to be an indicator of conditions during fetal development.…”
mentioning
confidence: 99%